The Influence of Slenderness in Steel and Composite Columns under Fire Conditions - Boursas, Farid; Boufarh, Rafik; Maghaghi, Bilal (Engineering, Technology & Applied Science Research, 2023)
This study simulated two columns using the finite element software SAFIR. The first was a steel profile column and the second was a steel profile partially encased in a concrete column (SPPEC). Both columns were heated on four sides for one hour using the ISO834 standard fire curve. Two boundary conditions were considered for both columns, simply and doubly supported and loaded utilizing eccentric loading. A parametric analysis aimed to identify a thermal analysis of unprotected and protected steel columns in terms of temperature field distribution, and time-temperature curves of a few selected nodes were drawn from the SAFIR software. A thermomechanical study was also carried out using the results of the thermal analysis to determine the influence of slenderness on the resistance of the steel and the partially encased profile in concrete columns under fire solicitation. Finally, a comparison of the fire resistance of the two columns was made. The results proved that the slenderness negatively influences the fire resistance of the steel and composite columns and that the behavior of the composite columns is significantly better than the steel ones.